Brain serotonin and serotonin transporter expression in male and female postnatal rat offspring in response to perturbed early life dietary exposures - Ye, Xin; Ghosh, Shubhamoy; Shin, Bo-Chul; Ganguly, Amit; Maggiotto, Liesbeth; Jacobs, Jonathan P.; Devaskar, Sherin U. (Frontiers in Neuroscience, 2024)
Serotonin (5-HT) is critical for neurodevelopment and the serotonin transporter (SERT) modulates serotonin levels. Perturbed prenatal and postnatal dietary exposures affect the developing offspring predisposing to neurobehavioral disorders in the adult. We hypothesized that the postnatal brain 5-HT-SERT imbalance associated with gut dysbiosis forms the contributing gut-brain axis dependent mechanism responsible for such ultimate phenotypes. Employing maternal diet restricted (IUGR, n=8) and high fat+high fructose (HFhf, n=6) dietary modifications, rodent brain serotonin was assessed temporally by ELISA and SERT by quantitative Western blot analysis. At early postnatal (P) day 2 no changes in the IUGR, but a ~24% reduction in serotonin (p=0.00005) in the HFhf group occurred, particularly in the males (p=0.000007) revealing a male versus female difference (p=0.006). No such changes in SERT concentrations emerged. At late P21 the IUGR group reared on HFhf (IUGR/HFhf, n=4) diet revealed increased serotonin by ~53% in males (p=0.0001) and 36% in females (p=0.023). While only females demonstrated a ~40% decrease in serotonin (p=0.010), the males only trended lower without a significant change within the HFhf group (p=0.146). SERT on the other hand was no different in HFhf or IUGR/RC, with only the female IUGR/HFhf revealing a 28% decrease (p=0.036). In simultaneous colonic microbiome studies, serotonin-producing Bacteriodes increased with decreased Lactobacillus at P2, while the serotonin-producing Streptococcus species increased in IUGR/HFhf at P21. Sex-specific changes emerged in association with brain serotonin or SERT in the case of Alistipase, Anaeroplasma, Blautia, Doria, Lactococcus, Proteus, and Roseburia genera. We conclude that an imbalanced 5-HT-SERT axis during postnatal brain development is sex-specific and induced by maternal dietary modifications related to postnatal gut dysbiosis. We speculate that these early changes albeit transient may permanently alter critical neural maturational processes affecting circuitry formation, thereby perturbing the neuropsychiatric equipoise.